Advancing higher education with GenAI: factors influencing educator AI literacy - Ayyoub, Abedalkarim M.; Khlaif, Zuheir N.; Shamali, Mahmoud; Abu Eideh, Belal; Assali, Alia; Hattab, Muayad K.; Barham, Kefah A.; Bsharat, Tahani R. K. (Frontiers in Education, 2025)
Artificial Intelligence (AI) literacy has emerged as a critical skill across various disciplines and industries, including education. This study aimed to identify the factors that influence educators' AI literacy and to examine the relationships among these factors. A sequential mixed methods approach was used to investigate the factors influencing faculty members' AI literacy, with qualitative data collected from 33 faculty members through focus group discussions and semi-structured interviews. Quantitative data were then gathered using the finalized survey instrument, completed by 538 faculty members from diverse disciplines and higher education institutions in Palestine. Data analysis was conducted using Smart PLS. The findings revealed several key factors that impact educators' AI literacy, including AI competencies, perceived usefulness of AI, ease of use, professional development, and community support. Additionally, prior experience with technology played a significant role in developing AI literacy. While the study's mixed methods design provided depth, one limitation was that the qualitative phase involved a relatively small sample. Future research should further explore the broader implications of AI in education and its integration across various academic fields.